The Effects of Technical and Fundamental Factors on the Investment Decision and the Company Value in the Agricultural Sector - Mamay Komarudin; Naufal Affandi (Quantitative Economics and Management Studies, 2020)
This study aims to analyze the influences of technical variables, which consist of the stock price and the Total Volume Activity (TVA), as well as fundamental variables, which consist of the Price Book Value (PBV) and the Debt to Equity Ratio (DER) on the investment decisions and the company value measured by using the PER of some companies of agricultural sector listed in the Indonesian Stock Exchange. Path analysis is used as the data analysis method. The research results show that one of the technical factors that significantly influences the investment decision and the company value is the stock price. Meanwhile, one of the fundamental factors that influences the investment decision and the company value is the PBV. The hypothesis testing showing that the stock price factor and the PBV factor have positive effects on the value of agricultural sector company is proven or accepted. On the other hand, the other variables, according to theorema trimming, are proved to be not includable in the path calculation if the path is proved to be insignificant, in this case the DER and the trading volume variable